In-vitro proliferation of Musa balbisiana improves with increased vitamin concentration and dark culturing - Ssekiwoko, F.; Talengera, D.; Kiggundu, A.; Namutebi, M.K.; Karamura, E.B.; Kunert, Karl J. (Open Science Publishers LLP (India), 2014)
Musa balbisiana is a wild banana genotype with important traits such as drought tolerance and disease resistance. Uniform and clean plants are often required to study these traits in different laboratories but plants can only be generated through a tissue culture process yet for a long time a protocol for regeneration of the same has not been available. Here, we demonstrate that modification of the anti-oxidant content of the in- vitro plant proliferation medium through adjusting the concentration of ascorbic acid and thiamine HCl in the basal MS medium together with subjecting the explants to dark culturing conditions improved proliferation of M. balbsiana by over 10 fold. These treatments resulted in 40 shoots per initial explant material at the best performance.